Faktor Pertimbangan Pernikahan Dini dan Strategi Pencegahan: Early Marriage Consideration Factors and Prevention Strategies - Harsoyo; Rahmad Purwanto Widyastomo (LPPM Universitas 17 Agustus 1945 Semarang, 2022)
This paper aims to identify the determinant factors that trigger early marriage and strategies to prevent early marriage as a targeted prevention intervention in Semarang City. The method used is quantitative research using analytic descriptions. The results showed that early marriage in the city of Semarang was not caused by economic problems, but because of incidents of pregnancy out of wedlock. The main driving factors for early marriage related to this are psychological factors: 80%, social and social: 79% and culture in society: 77% and low knowledge related to marriage and sexuality: 61%. This study recommends the provision of comprehensive and inclusive Sexual and Reproductive Health Rights ( SRHR) education for all children, increasing public awareness in supervising violations of norms and values, increasing the capacity of Karang Taruna as part of the community's economic drive, increasing social bonds and family bonds in protecting children from the bad effects of promiscuity, improving the quality of education and the economy of early marriage actors through skills training through a smartphone and internet-based digital economy, as an effort to create jobs that are practical, economical and applicable.